PEMBERIAN DOSIS INOKULUM JAMUR MIKORIZA ABUSKULA (JMA) DAN PUPUK P YANG BERBEDA TERHADAP SERAPAN P DAN PERTUMBUHAN TANAMAN JAGUNG (Zea mays L.) - Givani Oktaviana; Yusran Yusran; Wahyu Harso (Biocelebes, 2019)
The effectivity of Arbuscular Mycorrhizal (AM) Fungi to increase P absorption is not only affected by AM fungal inoculum dose but also affected by soil P concentration. The aim of this study was to observe the effect of AM fungus inoculum doses and appropriate P concentration added in soil to increase maize growth. The study was conducted with completely randomized design based on two factors i.e. dose of AM fungus inoculums (0, 10, 20 g/polybag) and different P fertilizer levels (0, 1,8, 0,37 and 0,74 g/polybag). Gigaspora margarita species was used as a fungus inoculum. A polybag contained 5 kg air-dried soil. The results showed that application of AM fungus inoculum increased plant growth in low P soil while it did not increase plant growth in high P soil. Increasing fungus inoculum dose did not increase plant growth since the rate of root colonization was not significantly different.